Florida harvester ant nest architecture, nest relocation and soil carbon dioxide gradients. - Walter R Tschinkel (PLoS ONE, 2013)
Colonies of the Florida harvester ant, Pogonomyrmex badius, excavate species-typical subterranean nests up the 3 m deep with characteristic vertical distribution of chamber area/shape, spacing between levels and vertical arrangement of the ants by age and brood stage. Colonies excavate and occupy a new nest about once a year, and doing so requires that they have information about the depth below ground. Careful excavation and mapping of vacated and new nests revealed that there was no significant difference between the old and new nests in any measure of nest size, shape or arrangement. Colonies essentially built a replicate of the just-vacated nest (although details differed), and they did so in less than a week. The reason for nest relocation is not apparent. Tschinkel noted that the vertical distribution of chamber area, worker age and brood type was strongly correlated to the soil carbon dioxide gradient, and proposed that this gradient serves as a template for nest excavation and vertical distribution. To test this hypothesis, the carbon dioxide gradient of colonies that were just beginning to excavate a new nest was eliminated by boring 6 vent holes around the forming nest, allowing the soil CO2 to diffuse into the atmosphere and eliminating the gradient. Sadly, neither the nest architecture nor the vertical ant distribution of vented nests differed from either unvented control or from their own vacated nest. In a stronger test, workers excavated a new nest under a reversed carbon dioxide gradient (high concentration near the surface, low below). Even under these conditions, the new and old nests did not differ significantly, showing that the soil carbon dioxide gradient does not serve as a template for nest construction or vertical worker distribution. The possible importance of soil CO2 gradients for soil-dwelling animals is discussed.